POLA PERSEBARAN DAN PENGELOLAAN MATA AIR UNTUK PENYEDIAAN AIR RUMAH TANGGA BERKELANJUTAN DI DESA NAGARI TANJUNG BARULAK KECAMATAN BATIPUH KABUPATEN TANAH DATAR - gilang gilang ramadan; Helfia Edial (JURNAL BUANA, 2026)
This study aims to obtain data, analyze, and discuss the Distribution pattern and Management of spring for Sustainable Household Water Supply in the Village of Nagari Tanjung Barulak, Batipuh District, Tanah Datar Regency. This type of research survey, interviews and questionnaires There are 4 techniques for collecting information. The data were analyzed using the nearest neighbor method of 7 springs discharge, analyzing the quality of spring water and knowing how to manage the community in utilizing springs (PAMSIMAS) whit a total Households population of 1300 heads of household with 42 subjects as subject questionnaires, documentation and interviews for clean water in Kenagarian Tanjung Barulak. From the results of the study, it can be concluded that the distribution pattern of the springs in Kenagarian Tanjung Barulak is classified as random in the nearest neighbor analysis with anNR value of 1.163848 while the quality of the springs is analyzed by using physical, chemical (pH) and biological Laboratory test, and the results of meet the standard Provisions set by the regulations of the Ministry of Health The Republic of Indonesia it can be concluded he water in the 3 springs is fit for drinking. For springs discharge Using the buckets method, the results are 2 classes V( 1 Liter/second to 10 Liter/second ) and class VI( approximately 0.1 Liter/second to 1Liter/second ), furthermore then to find out community management in managing springs using a sequential explanatory strategy method, the population of this stud we respondent who used springs water needs springs (PAMSIMAS) by the Kenagarian Tanjung Barulak community with the subjects Answering 28% Very Sufficient, 48% Sufficient and 24% Not Sufficient and for community Action towards the action of water sources the Kenagarian Tanjung Barulak community caries out Gotong royong cleaning around the springs such as dry leaves or twigs and as soon as possible repair the damage so that the distribution of the springs is not disturbed